СРАВНИТЕЛЬНО-ВОЗРАСТНОЙ АНАЛИЗ ПРИРОСТА ОБЪЕМА СЛОВАРЯ У НОРМАЛЬНО РАЗВИВАЮЩИХСЯ ДЕТЕЙ В ВОЗРАСТЕ ОТ 4 ДО 9 ЛЕТ - Королева, Е М; Вишонкина, А А; Волощенко, А А; Горчакова, А П; Кузнецова, В А; Петрунина, М А; Писаренко, А В; Новожилова, П Р; Хагажеева, Д В (FORCIPE, 2020)